2018
DOI: 10.1155/2018/1284687
|View full text |Cite|
|
Sign up to set email alerts
|

From Localized Scleroderma to Systemic Sclerosis: Coexistence or Possible Evolution

Abstract: Background Systemic sclerosis (SSc) and localized scleroderma (LoS) are two different diseases that may share some features. We evaluated the relationship between SSc and LoS in our case series of SSc patients. Methods We analysed the clinical records of 330 SSc patients, in order to find the eventual occurrence of both the two diseases. Results Eight (2.4%) female patients presented both the two diagnoses in their clinical histories. Six developed LoS prior to SSc; in 4/6 cases, the presence of autoantibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…W wielu pracach zwraca się uwagę, że w zależności od odmiany klinicznej LoSc mogą pojawić się objawy pozaskórne [3,6]. W świetle aktualnej wiedzy LoSc nie ulega progresji do twardziny układowej (systemic sclerosis -SSc), należy jednak pamiętać o możliwości współistnienia obu chorób [1,5,7].…”
Section: Etiopathogenesisunclassified
See 1 more Smart Citation
“…W wielu pracach zwraca się uwagę, że w zależności od odmiany klinicznej LoSc mogą pojawić się objawy pozaskórne [3,6]. W świetle aktualnej wiedzy LoSc nie ulega progresji do twardziny układowej (systemic sclerosis -SSc), należy jednak pamiętać o możliwości współistnienia obu chorób [1,5,7].…”
Section: Etiopathogenesisunclassified
“…Many papers emphasize the fact that depending on the clinical type of LoSc, extracutaneous manifestations may appear [3,6]. According to the current state of knowledge, LoSc does not progress into systemic sclerosis (SSc); however, it should be remembered that both diseases might co-exist [1,5,7].…”
mentioning
confidence: 99%
“…Pharmacopuncture involves stimulation of acupoints with an injection of herbal medicines in TKM and TCM; it exhibits more rapid efficacy than oral administration because the drug does not pass through the digestive system, and is frequently used for the regulation of immune balance in clinical settings. [4,5] The patient had previous experience with bee venom pharmacopuncture due to shoulder pain. Thus, to relieve rapidly worsening localized skin symptoms by using immune regulation, we selected bee venom pharmacopuncture.…”
Section: Case Reportmentioning
confidence: 99%
“…[1,2] While the association of morphea and systemic sclerosis (SSc) is considered to be a rare condition, several studies have reported their coexistence or possible coevolution. [3,4]…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled “From Localized Scleroderma to Systemic Sclerosis: Coexistence or Possible Evolution” [ 1 ], the first and last names of all the authors were reversed. The revised authors' list is shown above.…”
mentioning
confidence: 99%